High-Fat Diet Obesity Associated With Insulin Resistance Increases Cell Proliferation, Estrogen Receptor, and PI3K Proteins in Rat Ventral Prostate - Ribeiro, Daniele Lisboa [UNESP]; Pinto, Maria Etelvina [UNESP]; Rafacho, Alex [UNESP]; Bosqueiro, Jose Roberto; Maeda, Samantha Yuri [UNESP]; Anselmo-Franci, Janete Aparecida; Taboga, Sebastiao Roberto [UNESP]; Goes, Rejane Maira [UNESP] (Amer Soc Andrology, Inc, 2012)
In this study, we evaluated the effects of obesity and insulin resistance induced by a high-fat diet on prostate morphophysiology, focusing on cell proliferation, expression of androgen (AR) and estrogen receptors (ER) and proteins of the insulin signaling pathway. Adult male Wistar rats were fed a high-fat diet (20% fat) for 15 weeks, whereas control animals received a balanced diet (4% fat). Both groups were then divided and treated for 2 weeks with 1 mg/kg body weight/day of the aromatase inhibitor letrozole or vehicle only. The ventral prostate was analyzed with immunohistochemical, histopathological, stereological, and Western blotting methods. Obese rats showed insulin resistance, hyperinsulinemia, and reduced plasma testosterone levels. The incidence of prostatic intraepithelial neoplasia (PIN) was 2.7 times higher in obese rats and affected 0.4% of the gland compared with 0.1% PIN areas found in control rats. Obesity doubled cell proliferation in both prostate epithelium and stroma. AR content decreased in the prostate of obese rats and estrogen receptor beta (ER beta) increased in this group. Protein levels of insulin receptor substrate 1 and protein kinase B diminished in the obese group, whereas phosphatidylinositol 3-kinase (PI3K) increased significantly. Most structural changes observed in the prostate of obese rats normalized after letrozole treatment, except for increased stromal cell proliferation and ER beta expression, which might be associated with insulin resistance. This experimental model of obesity and insulin resistance induced by a high-fat diet increases cell proliferation in rat prostate. Such alterations are associated with decreased levels of AR and increased ER beta and PI3K proteins. This change can facilitate the establishment of proliferative lesions in rat prostate.
Keywords: Androgen; fatty diet; cell hyperplasia